Malaria and an Amoebic Abscess in a Returning Traveler from Liberia - Mhd Mustafa Albitar; Nafiza Martini; Sandy Alkhalil; Tamim Alsuliman; Ali Alrstom (Case Reports in Infectious Diseases)
Malaria is an infectious Anopheles mosquito-borne disease caused by five different eukaryotic protozoa parasites. Amoebiasis is a parasitic infection caused by Entamoeba histolytica. Both diseases are widespread in Liberia. A returning traveler was diagnosed and treated for malaria, and 20 days later, an amoebic liver abscess was discovered, meaning that the malaria infection masked the amoebic infection, which emphasizes the importance of a complete examination of returning travelers, especially for those returning from Sub-Saharan Africa, where coinfections are more common. Herein, we propose that the relationship between Malaria and amoebic liver abscesses should be explored by researching the effects of malaria on ferritin levels and the immune components in the liver and whether it helps the emergence of hepatic amoebic abscesses or not.